Lowermost Mantle Anisotropy Beneath Africa From Differential SKS‐SKKS Shear‐Wave Splitting. Issue 8 (14th August 2019) - Reiss, M. C.; Long, M. D.; Creasy, N.
Abstract: We investigate seismic anisotropy in the lowermost mantle in the vicinity of the African large low shear velocity province (LLSVP) using observations of differential SKS ‐ SKKS shear‐wave splitting. We use data from 375 permanent and temporary stations in Africa which enable us to map the spatial distribution of the anisotropic regions of the lowermost mantle in unprecedented detail. Our results corroborate previous findings that anisotropy is most clearly observed at the margins of the LLSVP, indicating strong deformation at its border, and they are generally consistent with a mostly isotropic LLSVP interior. We find that most discrepant SKS ‐ SKKS measurements sample the lowermost mantle close to what is inferred to be the root of the Afar plume. We also identify strongly discrepant splitting in the vicinity of a previously mapped ultralow velocity zone (ULVZ) at the base of the LLSVP, beneath Central Africa. This represents an unusual observation of lowermost mantle anisotropy that is spatially coincident with a ULVZ and may reflect a unique anisotropic mechanism such as alignment of partial melt or the presence of strongly anisotropic magnesiowüstite. We interpret discrepant measurements outside of the LLSVP as likely reflecting a change in flow direction from the horizontal plane to a more vertical direction, which may be caused by deflection at the steep LLSVP border. We propose that our observations of D″ anisotropy associated with the African LLSVP can be explained by a mantle flow regime that maintains passive thermochemical piles with slab‐driven flow and allows for the formation of upwellings at their edges. Key Points: We present a comprehensive data set of discrepant SKS ‐ SKKS splitting observations to infer lowermost mantle anisotropy beneath Africa Measurements suggest deformation at the border of the African large low shear velocity province and local changes in mantle flow geometry Within the large low shear velocity province, anisotropy is associated with an ultralow velocity zone, which may also feed the Afar plume